Land law - Clarke, Sandra (Directions (Oxford, England), 2010)
This text is a lively introduction to land law, making this traditionally daunting subject both clear and engaging. All the key topics covered on an undergraduate course are explained with the use of helpful learning features, diagrams and photographs for a truly contemporary and student-centred approach